2020
DOI: 10.3329/birdem.v10i0.50994
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection of SARS-CoV-2: reports of three cases from a tertiary care hospital of Bangladesh

Abstract: Coronavirus disease 2019 (COVID-19) is a contagious respiratory and vascular disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). First identified in Wuhan, China, it has caused an ongoing pandemic. Some viruses give us lifelong immunity after first infection and initially researchers thought that SARS-CoV-2 infection may give lifelong immunity after first infection but few cases of reinfection are reported both locally and internationally. We report 3 symptomatic cases of reinfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The screening of 204 studies revealed that only 13 case reports from 9 countries studied COVID-19 reinfection [80][81][82][83][84][85][86][87][88][89][90][91][92] . Most of the reported cases included patients presented with typical COVID-19 symptoms at the time of reinfection.…”
Section: Reinfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The screening of 204 studies revealed that only 13 case reports from 9 countries studied COVID-19 reinfection [80][81][82][83][84][85][86][87][88][89][90][91][92] . Most of the reported cases included patients presented with typical COVID-19 symptoms at the time of reinfection.…”
Section: Reinfectionmentioning
confidence: 99%
“…Most of the reported cases included patients presented with typical COVID-19 symptoms at the time of reinfection. At reinfection time, eight patients presented with mild COVID-19 symptoms 81,83,84,86,[88][89][90] , two patients presented with moderate COVID-19 symptoms 85,91 , and four patients with severe COVID-19 symptoms 80,82,87,89 . However, one patient was asymptomatic at the time of the supposed reinfection 92 .…”
Section: Reinfectionmentioning
confidence: 99%
See 1 more Smart Citation